2005
DOI: 10.1177/154405910508400514
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Jaw Movement Affects Condylar Cartilage Development

Abstract: Using a mouse exo utero system to examine the effects of fetal jaw movement on the development of condylar cartilage, we assessed the effects of restraint of the animals' mouths from opening, by suture, at embryonic day (E)15.5. We hypothesized that pre-natal jaw movement is an important mechanical factor in endochondral bone formation of the mandibular condyle. Condylar cartilage was reduced in size, and the bone-cartilage margin was ill-defined in the sutured group at E18.5. Volume, total number of cells, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 28 publications
5
41
0
Order By: Relevance
“…After the operation, the fetuses together with the uterus were placed back in the abdominal cavity of the dam, and the incision on the abdominal muscle was sutured closed with 3-or 4-0 silk line; incision of the abdominal skin was closed by autosuture (MikRon 9 mm Autoclip Applier), and were allowed to develop exo utero till E18.5. As in our several previous studies (Hatta et al, 1994(Hatta et al, , 2002(Hatta et al, , 2004Habib et al, 2005Habib et al, , 2007Jahan et al, 2010), we observed that the exo utero surgery as described caused no general growth retardation, and neither the CRL, BW, nor the mandibular morphology of the E18.5 sham-operated fetuses were significantly different from those of the E18.5 in utero normal fetuses. Therefore, we here show only the results of sham-operated fetuses, and not those of in utero normal fetuses, as the control.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…After the operation, the fetuses together with the uterus were placed back in the abdominal cavity of the dam, and the incision on the abdominal muscle was sutured closed with 3-or 4-0 silk line; incision of the abdominal skin was closed by autosuture (MikRon 9 mm Autoclip Applier), and were allowed to develop exo utero till E18.5. As in our several previous studies (Hatta et al, 1994(Hatta et al, , 2002(Hatta et al, , 2004Habib et al, 2005Habib et al, , 2007Jahan et al, 2010), we observed that the exo utero surgery as described caused no general growth retardation, and neither the CRL, BW, nor the mandibular morphology of the E18.5 sham-operated fetuses were significantly different from those of the E18.5 in utero normal fetuses. Therefore, we here show only the results of sham-operated fetuses, and not those of in utero normal fetuses, as the control.…”
supporting
confidence: 84%
“…Prenatal TMJ movement restriction using the exo utero development system (Habib et al, 2005(Habib et al, , 2007Jahan et al, 2010) is a very strong form of mechanical stimulation to produce disharmony in the development of the mandible. This restriction of jaw movement clearly led to the morphological deformation of the mandible in the E18.5 sutured fetuses, and morphometric analysis in particular revealed a significant increase in the PD in the sutured group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). This regionalization method has been extensively used in studies on mandibular condylar cartilage (12)(13)(14)(15). The thickness of each zone was measured with Image-Pro Plus software.…”
Section: Compressive Mechanical Stress Loading On Rat Mandibularmentioning
confidence: 99%